The Internalızatıon of Islamıc Values on Undergraduate Students through the Baıtul Arqam - Noor Amirudin; Hasan Basri (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2020)
The purpose of this study is to find out the Islamic values internalized to the University of Muhammadiyah Gresik students who take Baitul Arqam and to find out the factors that influence the internalization of Islamic values to the University of Muhammadiyah Gresik (UMG) students who take Baitul Arqam. This study employed a qualitative approach that used observations, interviews, and documentation in data collection. The data was analyzed qualitatively through data reduction, data presentation, and verification. This research found that the internalization of Islamic values through the Baitul Arqam considered successful, in terms of cultivating morality, such as respecting lecturers and parents, the morals of fellow human beings, morals in doing daily interaction (mu’āmalah), as well as morality in worship. Supporting activities such as compulsory congregational prayers, sunnah prayers, and reciting Quran is also very important. Yet, there still needs to be a harder effort to motivate students to join Baitul Arqam wholeheartedly (ikhlās). Since this is a basis to gain knowledge according to Islamic perspectives.